Use of ICT in selected libraries in Ibadan, Oyo State, Nigerian (2012)
"This survey investigated the use of ICT in selected libraries in Ibadan, Nigeria. A structured questionnaire was developed to elicit information from the heads of the selected libraries on the use and application of ICT in their respective libraries. The data were collated, analyzed and interpreted based on standard statistical method. The results of the study revealed that libraries in Ibadan were at the developmental stage in the use of ICT for processing information services. This was found to be as a result of inadequate funding, poor infrastructural facilities and lack of requisite knowledge of ICt by most library personnel. Based on the outcome of the study, it was recommended that adequate funds be made available to the libraries for ICT implementations and library personnel be trained and retrained adequately to enhance ICT usage in libraries."